2017
DOI: 10.1039/c6gc03222b
|View full text |Cite
|
Sign up to set email alerts
|

Metal-catalyzed reductive deamination of glutamic acid to bio-based dimethyl glutarate and methylamines

Abstract: Glutamic acid was successfully converted into dimethyl glutarate and trimethylamine by a Pt based reductive deamination at 225 °C in methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…In the next sections various (bio)chemical conversion technologies for amino acids will be discussed (Figure ). Depending on the conversion technology and the target products, the substrate scope comprises either one amino acid, a selected mixture of amino acids or the entire protein hydrolysate …”
Section: Availability and Pretreatment Of Raw Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the next sections various (bio)chemical conversion technologies for amino acids will be discussed (Figure ). Depending on the conversion technology and the target products, the substrate scope comprises either one amino acid, a selected mixture of amino acids or the entire protein hydrolysate …”
Section: Availability and Pretreatment Of Raw Materialsmentioning
confidence: 99%
“…Moreover, the reaction was performed under a reducing atmosphere containing toxic H 2 S (20 vol %) to facilitate the elimination of NH 3 , though it is known that noble metal catalysts are easily deactivated by irreversible chemisorption of reduced sulfur species . Very recently, De Vos and co‐workers developed a two‐step chemocatalytic process for the deamination of glutamic acid to dimethyl glutarate and trimethylamine . In a first step, glutamic acid is modified to N , N ‐dimethylglutamic acid by a mild Pd‐catalyzed reductive N ‐alkylation in water using formaldehyde under H 2 atmosphere.…”
Section: Amino Acids As Direct Precursors To Value‐added Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…As amino acids to be key compounds in biomass refinery, there have also been some reports concerning conversion of amino acids into chemicals with solid additives. It was reported that Pt/TiO 2 promotes the reductive deamination of glutamic acid derivatives to form organic acids at 225°C for 24 h [54]. By the same research group of [54], decarbonylation of amino acids was attempted by Ru-based catalyst [55].…”
Section: Previous Studies On Solid Catalytic Reaction Of Amino Acid Imentioning
confidence: 99%
“…It was reported that Pt/TiO 2 promotes the reductive deamination of glutamic acid derivatives to form organic acids at 225°C for 24 h [54]. By the same research group of [54], decarbonylation of amino acids was attempted by Ru-based catalyst [55]. Reductive (hydrogenation) decarbonylation of valine to isobutylamine was developed in the presence of Ru-catalyst with isobutylamine yield of 87% in hydrothermal water at 150°C for 2 h.…”
Section: Previous Studies On Solid Catalytic Reaction Of Amino Acid Imentioning
confidence: 99%